As práticas etnomatemáticas de alunos ribeirinhos do rio Xingu como sinais de resistência à Hidrelétrica Belo Monte - FORMIGOSA, Marcos Marques (Universidade Federal do Pará, 2021)
The research in progress problematizes the forms of resistance, from the perspective of Ethnomathematics, of riverside students from the Xingu River in front of the implementation of Belo Monte. Part of the contributions of Wittgenstein, in his work of maturity, and his intertwining with ideas of Foucault. On the one hand, the first problematizes the language games generated in the different forms of life, pointing to the existence of family similarities between school mathematical models and those developed by riverside students. On the other hand, some notions of Foucault allow us to understand the regimes of truth present in the school, which marginalize other knowledge. The expected results, from the immersion in the field, should point to the forms of resistance of the riverside dwellers, present in their mathematical language games arising from their daily practices and in the permanence of the riverside dwellers in the place, from the maintenance of the school as a guarantee access to education as a right.